OP32 Using twitter to explore advance care planning among brain tumor stakeholders. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Lum, H; Cutshall, N; Salmi, L; Berry, R; Kwan, B
Abstract : Background: Advance care planning (ACP) often occurs too late in the disease course of patients affected by brain tumors. Furthermore, the perspectives of brain tumor stakeholders on ACP are not well described. This study uses a social media tweet chat to understand perspectives on ACP among brain tumor stakeholders. Methods: This qualitative descriptive study analyzed a tweet chat (real-time virtual group discussion on the social media platform Twitter) of brain tumor stakeholders. The 1-hour tweet chat was organized by the patient-run Twitter community referred to with the hashtag #BTSM, which stands for Brain Tumor Social Media. Participants reflected on four questions about ACP by including #BTSM in tweets. Unique tweets and stakeholder type (i.e. patient, caregiver, advocate or organization member, clinical provider and researcher, leader) were categorized. The tweet chat transcript was analyzed to identify key themes. Results: Fifty-two participants from four countries contributed 336 unique Tweets. Most participants were patients, clinical providers or researchers, and advocates or organizations. There were four key themes regarding brain tumor stakeholder perspectives about ACP: 1) cultural barriers prevent discussions of death; 2) ensuring one's voice is heard; 3) Goldilocks' approach to timing – fearing ACP is too early or too late; and 4) crowdsourcing ACP resources. Conclusions: A multi-national group of brain tumor stakeholders engaged in ACP discussions via a social media tweet chat and highlighted important challenges and opportunities. Social media is a new avenue in which clinicians and patients may engage with to better understand each other's perspectives related to ACP.